Management of a case of symblepharon by freshly prepared amniotic membrane transplantation: a clinical case report - Baruah, Mamoni; Das, Rajiv Kr.; Dam, Bikram; Nandi, Sunanda (International Journal of Research in Medical Sciences, 2020)
Amniotic membrane transplantation has been in common therapeutic use for a variety of ocular disorders. Authors present a case of a 50-year-old man who was diagnosed to be a case of total symblepharon following an episode of membranous conjunctivitis who was treated with freshly prepared Amniotic membrane transplantation with satisfactory cosmetic result.